Removal of Complete Spontaneous Migration of an Intrauterine Contraceptive Device to the Bladder by Cystoscopy - Akbar Novan Dwi Saputra; Muhammad Nurhadi Rahman; Anis Widyasari (Hindawi Limited, 2024)
Intrauterine contraceptive devices (IUCD) are widely used as a reversible method of contraception. Although uterine perforation caused by an IUCD is rare, in some cases, the device may migrate to the pelvic/abdominal cavity or nearby structures. When the IUCD migrate to the bladder, it can lead to various symptoms. These include pain or discomfort in the lower abdomen, difficulties or pain during urination, frequent urinary tract infections, and the development of bladder stones. This article presents a case report of a 24-year-old woman with an intrauterine contraceptive device (IUCD) that had migrated completely into the bladder. She had an IUCD inserted by a midwife four years earlier and became pregnant a year later, unaware of the IUCD's presence. She later presented with lower abdominal pain, hematuria, and dysuria three months before being admitted to our hospital. Imaging confirmed the intravesical location of the IUCD. She underwent successful cystoscopy treatment to remove the migrated IUCD. Prompt diagnosis and appropriate management are crucial in preventing complications and improving patient outcomes. Clinicians should be aware of this potential complication and consider it when patients present with symptoms or complications after IUCD insertion. Regular monitoring and timely intervention can help detect and address IUCD migration effectively.